Two-plasmon-decay instability stimulated by dual laser beams in inertial confinement fusion - C.-W. Lian; Y. Ji; R. Yan; J. Li; L.-F. Wang; Y.-K. Ding; J. Zheng (Matter and Radiation at Extremes)
Two-plasmon-decay instability (TPD) poses a critical target preheating risk in direct-drive inertial confinement fusion. In this paper, TPD collectively driven by dual laser beams consisting of a normal-incidence laser beam (Beam-N) and a large-angle-incidence laser beam (Beam-L) is investigated via particle-in-cell simulations. It is found that significant TPD growth can develop in this regime at previously unexpected low laser intensities if the intensity of Beam-L exceeds the large-angle-incidence threshold. Both beams contribute to the growth of TPD in a “seed-amplification” manner in which the absolute instability driven by Beam-L provides the seeds that are convectively amplified by Beam-N, making TPD energetically important and causing significant pump depletion and hot-electron generation.